Mimetic, Coercive and Normative Influences and the Decision of National Sport Organisations to Bid for World Championship Events - Johnston, Mel (Auckland University of Technology, 2013)
This research investigates the coercive, mimetic and normative pressure on a National Sport Organisation’s (NSO) decision to bid for a world championship event. New Zealand is progressively establishing itself as a leader in hosting international sport events. Whilst government and their sport agencies contribute much to the process, the entire process is reliant upon a NSO submitting a bid to host the event. DiMaggio and Powell’s (1983) three forms of institutional pressures that cause organisations to conform; coercive, mimetic and normative, were employed to understand the NSO decision to bid. An interpretive approach was taken for the research, and involved a multiple-case study approach. The research participants were comprised of six key decision makers from three New Zealand NSOs that had bid for world championship event, but the event was yet to have taken place. Thematic analysis was employed to provide inductive analysis of the data collected from the participant’s responses. The key finding of the research is that direct and explicit institutional pressures were not seen to significantly influence a NSOs decision whether to bid for a world championship event. However, indirect and implicit coercive, mimetic and normative pressures were evident within this context, and provided a subtle influence on a NSOs decision to bid. The results of this research contribute to the theoretical knowledge of institutional pressures within the sport context, as well as providing New Zealand NSOs, and their stakeholders, with a clearer understanding of the dynamics underpinning the NSO decision to bid for a world championship event.
Keywords: Mimetic; Coercive; Normative; World championship event; Sport event; Institutional